Conference – 1992 Equation (4)

E P ˙ = f ( P t P t 1 ) , where f > 0 MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGcbaGaamyraiqadc fagaGaaiabg2da9iaadAgadaqadaqaaiaadcfadaWgaaWcbaGaamiD aaqabaGccqGHsislcaWGqbWaaSbaaSqaaiaadshacqGHsislcaaIXa aabeaaaOGaayjkaiaawMcaaiaacYcacaWG3bGaamiAaiaadwgacaWG YbGaamyzaiaaykW7caWGMbWaaSbaaSqaaiaaikdaaeqaaOGaeyOpa4 JaaGimaaaa@4C43@